(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Chronic otitis media is a persistent inflammatory condition of the middle ear mucosa and mastoid air cell system. The disease may result in hearing impairment and potentially serious complications, including intracranial involvement. Although hearing loss and otorrhea are typical clinical manifestations, tinnitus is a functional symptom that may exert a profound and long-lasting impact on health-related quality of life. The aim of this study was to evaluate the extent to which tinnitus affects quality of life in adult patients with chronic otitis media. Methods: A cross-sectional study was conducted on 70 patients aged ≥18 years diagnosed with chronic otitis media and indicated for surgical treatment at Viet Tiep Friendship Hospital, Hai Phong, in 2025. Results: The impact of tinnitus on quality of life was predominantly moderate (54.3%); however, 18.6% of cases were classified as severe or catastrophic. The most affected domains included sleep disturbance (20.0%), depressive feelings (17.1%), and impaired concentration (11.4%). Conclusion: Tinnitus in patients with chronic otitis media is not only persistent but also significantly impairs quality of life, particularly in the domains of sleep, emotional well-being, and cognitive performance.